Urban Labelling: Resilience and Vulnerability as Key Concepts for a Sustainable Planning - Mazzeo, Giuseppe (TeMA - Journal of Land Use, Mobility and Environment, 2014)
Planning and implementation of sustainable urban neighborhoods has led in Europe and in other countries to the development of some recognized best practices. Each of these cases has followed specific aims and methodologies but it is still far the systematization of the results and the translation of the good practices into action lines. The paper involves the necessity of new tools for local planning directed to the overall sustainability of the city. Sustainable energy, reduction of the climate-change causes, waste reduction, attention to water resources and to the natural ones are specific operational elements. A possible way to face this challenge is to consider the potentialities of executive plans addressed to increase the sustainability of urban areas starting from limited portions of they. These plans should foresee the minimum impact of volumes and functions to be set up, will provide for the realization of public spaces with zero or almost zero impact, will promote the integration of all the technologies to reduce consumption and encourage energy generation, in order to increase the resilience of the city reducing its vulnerability. On this basis, aim of the paper is to deepen the issue of the measure of the expected results. To this purpose it is necessary to structure a new certification system (Urban Labelling) that can be able to assign a specific sustainability level to a plan using both traditional and new indexes. The same system can also be applied to existing urban areas and as a basis for evaluating reward operations. The impact of the new tool will be cultural (to switch by a description to the facts in relation to urban sustainability), economic (to involve the supply chain from design, implementation, and urban transformation) and technological (the sustainability of urban areas requires the use of advanced technologies not only for the buildings but also in the control of green areas, public spaces and mobility).